2009
DOI: 10.1089/jpm.2008.0228
|View full text |Cite
|
Sign up to set email alerts
|

Rural Palliative Care: A Comprehensive Review

Abstract: Background: Access to integrated, palliative care regardless of location of residence is a palliative care standard yet we know such access is limited for those living in rural and remote settings. As a beginning step in the development of research aimed at informing policy and program development, a comprehensive review of the state of knowledge regarding palliative care in rural contexts is required. Purpose: To identify, evaluate and synthesize the published literature on rural palliative care. Design: Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
137
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 65 publications
4
137
0
Order By: Relevance
“…2 Instead, the focus of research in end-oflife decision-making has centered around urban populations. 2,3 Nevertheless, given important differences between urban and rural populations, medical practitioners should not assume that taking care of rural patients at the end of life is no different from caring for urban patients at the end of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Instead, the focus of research in end-oflife decision-making has centered around urban populations. 2,3 Nevertheless, given important differences between urban and rural populations, medical practitioners should not assume that taking care of rural patients at the end of life is no different from caring for urban patients at the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…2 Instead, the focus of research in end-oflife decision-making has centered around urban populations. 2,3 Nevertheless, given important differences between urban and rural populations, medical practitioners should not assume that taking care of rural patients at the end of life is no different from caring for urban patients at the end of life. 4 With the aging of rural populations, assessing the end-of-life preferences of rural elderly patients is critical for planning and providing palliative care and hospice services for diseases that 1 this underserved population is likely to confront.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schrader et al 2 surveyed colleagues about programs in South Dakota but did not include any program characteristics. Robinson et al 3 surveyed all the evidence in multiple countries but found little programmatic data and concluded: ''. .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are numerous resources reviewing the role of primary health practitioners in rural practice (Canadian Association for Rural and Remote Nursing, 2008;MacLeod et al, 2008 ;Misener et al , 2008;Pong & Pitblado, 2005;Romanow, 2002), along with articles reviewing palliative care needs in rural settings (Crooks, Castleden, Schuurman, & Hanlon, 2009;Downing & Jack, 2012;Evans, Stone, & Elwyn, 2003 ;Robinson et al , 2009). What has been less apparent is guidance for the unique role that FNPs have in facilitating a good death, particularly within rural settings.…”
mentioning
confidence: 99%